Educar en la autonomía moral: una obligación para los docentes y una necesidad para los estudiantes del siglo XXI - Peñarrieta Juanito, Maria Alejandra (2013)
This work develops an analysis about theimportance of moral autonomy educationin students through an education based invalues. It is expected taking to the reflectionthrough the observation of important aspectsthat deal with a great challenge contributing tothe improvement of the real social problem.